Factors in homeowners’ willingness to adopt nitrogen-reducing innovative/alternative septic systems - Rudman, Alexie N.; Mulvaney, Kate K.; Merrill, Nathaniel H.; Canfield, Katherine N. (Frontiers in Marine Science, 2023)
When environmental mitigation requires individual adoption, engagement approaches centered on cost effectiveness and technological efficiency alone are often insufficient. Through focus groups with adopters and prospective adopters, this research identifies factors influencing homeowners’ willingness to adopt Innovative/Alternative (I/A) septic systems for nitrogen reduction. We apply concepts from technology adoption and behavior change models as a framework for illustrating the homeowner decision-making process around I/A adoption. The perceived needs to replace an old/failing septic system, comply with local regulations, and protect local water quality synergistically catalyzed adoption. Adoption was further influenced by the larger context within which it is taking place, perceived characteristics of I/A systems and the installation process, system aesthetics concerns, and homeowners’ attitudes and beliefs. Considering how these factors affect adoption could enable resource managers to design more targeted interventions to encourage adoption through behavior change strategies such as social marketing, and to improve how these systems are communicated. If I/A systems are to be used as a tool to achieve water quality goals, the considerations influencing homeowners’ willingness to install these systems will be critical to incentivizing voluntary adoption. Many of these factors are relevant to the adoption of other individual-level environmental management strategies, which are being increasingly deployed in response to complex, nonpoint source pollution issues.